PENJATUHAN SANKSI PIDANA KETENAGAKERJAAN TERDAHAP DELIK MEMPEKERJAKAN ANAK PADA PEKERJAAN TERBURUK: STUDI PUTUSAN NOMOR 322/PID.SUS/2020/PN. TULUNGAGUNG - Pratama, Rio Arif Pratama; Zanah, Ana Noer (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The purpose of this study is to find out and understand the application of fair criminal sanctions for victims employed by defendants in nightlife venues. It also aims to understand legal considerations by judges in imposing a prison sentence on the defendant. This research is a doctrinal type with secondary data. The secondary data that the author reviewed is the Tulungagung District Court Decision Number: 322/Pid.Sus/2020/PN. Tulungagung, as well as legal materials consisting of primary legal materials such as Law Number 23 of 2002 concerning Child Protection, Law Number 13 of 2003 concerning Manpower. The data collection technique is a literature study and uses a deductive method in analyzing the author’s data. The result of this study is that the Panel of Judges tends to prioritize procedural justice over substantive justice. This means that the panel of judges tends to be based on the provisions of laws and regulations and does not delve into more in-depth legal facts of the trial. That it was not submitted by an expert in the trial also had an effect on proving the crime of employing children in the worst job and employing children at 23.00 to 07.00, so that the victim did not get substantive justice.